Seismic behavior of variable friction timber dampers: Experimental and numerical investigation. (1st August 2022) - Wu, Ya-Jie; Xie, Qi-Fang; Lin, He-Shou; Zhang, Li-Peng; Yang, Hui-Feng
Abstract: This paper proposed variable friction timber dampers (VFTDs) made of replaceable grooved timber plates, seismic behavior of such dampers and its influence on the lateral performance and dynamic response of heavy timber frames were investigated. Firstly, in total four specimens with different geometry characteristics and pre-stressing forces were conducted with reversed cyclic loading test. Typical damage and failure modes were identified and hysteretic curves were analyzed. Secondly, a modelling method on the hysteretic behavior of VFTDs was proposed by using multiple materials in OpenSees. Combined an existing test of a simple timber frame, the lateral performance and dynamic response of timber frames with VFTDs were numerically investigated and compared to those of a simple frame and a frame with a conventional friction timber damper. The experimental results indicated that timber plates of VFTDs cracked perpendicular to wood grain under combined compression and friction. The cracking weakened the integrity of timber plates, resulting to asymmetry of hysteretic curves of VFTDs. VFTDs were able to dissipate energy meanwhile provide higher damping force when timber plates slid on slope surfaces. Increasing pre-stressing force in a certain range considerably improved damping force and energy dissipation capacity of VFTDs. The numerical simulation demonstrated that VFTDs increased the lateral load-resisting capacity and energy dissipation capacity of timber frames more than 55% and 710%, respectively. Owing to superior lateral load-resisting capacity and extraordinary energy dissipation capacity of VFTDs, the peak drift and acceleration of timber frames decreased up to 55%. VFTDs with slope sliding surfaces outperformed VFTDs with consecutive flat and slope sliding surfaces and conventional friction timber dampers in seismic response reduction. Highlights: Variable friction timber dampers made of replaceable grooved timber plates were proposed and tested. A method was proposed to model the seismic behavior of variable friction timber dampers in OpenSees. Seismic response of timber frames with/without variable friction timber dampers were numerically investigated and compared.